2019
DOI: 10.1024/1422-4917/a000652
|View full text |Cite
|
Sign up to set email alerts
|

Die Rolle der morphologischen Bewusstheit bei Lese- und Rechtschreibleistungen

Abstract: Zusammenfassung. Fragestellung: Obwohl die morphologische Bewusstheit (MB) eine wichtige Rolle beim Schriftspracherwerb spielt, ist sie im deutschsprachigen Raum wenig untersucht und es gibt keine publizierten Testverfahren dafür. Diese Studie untersucht den Zusammenhang der MB mit verschiedenen Maßen der Lesefähigkeit, mit der Rechtschreibfähigkeit und der phonologischen Bewusstheit (PB) bei deutschsprachigen Kindern. Methodik: Um die MB zu erheben, wurde ein MB-Screening entwickelt. 172 Zweitklässler wurden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…In line with our prediction, morphological awareness accounted for more variance in spelling than in reading fluency. This goes in line with recent results reported by Volkmer et al (2019), who also found significant contribution of morphological awareness on spelling for the German orthography and by Desrochers et al (2018), who emphasised the influence of morphological awareness on spelling for the consistent Greek orthography. In German, the contribution of morphological awareness on spelling is likely to result from the strong asymmetry in German orthography, which is characterised by clearly lower phoneme-grapheme consistency (spelling direction) than grapheme-phoneme consistency (reading direction).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with our prediction, morphological awareness accounted for more variance in spelling than in reading fluency. This goes in line with recent results reported by Volkmer et al (2019), who also found significant contribution of morphological awareness on spelling for the German orthography and by Desrochers et al (2018), who emphasised the influence of morphological awareness on spelling for the consistent Greek orthography. In German, the contribution of morphological awareness on spelling is likely to result from the strong asymmetry in German orthography, which is characterised by clearly lower phoneme-grapheme consistency (spelling direction) than grapheme-phoneme consistency (reading direction).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the current findings add to the existing literature by showing that morphological awareness predicts reading and spelling in a consistent orthography. While the total amount of variance explained in reading is rather small, the amount of variance explained in spelling is comparable with prior research in consistent orthographies (Desrochers et al 2018; Volkmer et al 2019), although smaller than reported in less consistent orthographies (Desrochers et al 2018). The inclusion of further relevant predictors such as RAN instead of sublexical orthographic sensitivity is expected to increase the total amount of variance accounted for in the models, especially for reading fluency.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations